legal Strictures in the Management and Development of Orphans Monies in Palestine - Anas Yousef jazzar (My University, 2016)
In this study we dealt with the theme of "legitimate controls in the management and development of orphans funds study applied Ramallah and Hebron model." I threw off the light on the extent of interest in Islamic jurisprudence old and new orphans, in terms of care, and it is to preserve the rights of both financial and private, and how to invest their money and development within the roads and controls legitimacy and through sponsorship, and care, and education, and discipline, and the campus of the attack on their rights in any way. Stewardship of orphans in Islam and the legitimate demand of the Holy Quran ceremony of remembrance of many of the provisions and homilies that relate to the person of the orphan, and was I have divided this research to the forefront, and smooth, and four chapters, and a conclusion has shown through these four methods of orphan care money chapters that you know the orphan and the governor to get to the best legitimate ways to invest the wealth of the orphan and development. I talked in the first quarter for the definition of an orphan and idiomatically language and the importance of state funds addressed in the second section of this chapter to the definition of the state and its divisions and those found to have jurisdiction over the wealth of the orphan, either in the third section grabbed Terms guardian on the wealth of the orphan, and authority to dispose of that money so as not to be the aggressors on the wealth of the orphan, and to act with his money, but one that is better. The second chapter was titled the legality of the investment in the orphan's wealth. This chapter is divided into two sections main, I spoke in the first section on the concept of investment in the language of the Arabs and the term legal scholars and economists, but in the second requirement touched on the legality of the investment of the basic legislation sources, commenting on and explaining, and concluded this topic by mentioning the rule of investment funds in orphans Based on the evidence of those who reported from the Koran and the Sunna on its legitimacy. In the second part, the most important legitimate purposes stated in the investment funds orphans touching Makassed rules for the control of financial transactions and related legislation and the organization of the funds in the first requirement, either in the second most important investment demand Vaakect controls related to money orphan whether they legitimate or even legal and administrative. The third chapter was titled Orphans Fund Investment ways. This chapter is divided into two sections the two principal, showed in the first part, the ruling on eating the guardian of the wealth of the orphan and the actions of the guardian money orphan in the financial trade-offs decades, such as speculation and Almsacap and the farmer and the rest of jurisprudence regarding the sale of the guardian of the wealth of the orphan. The fourth chapter is the most important chapters in my research this if it is the fruit and extract research, where he was titled a field study on the management and development of Foundation Amol orphans in Palestine, as discussed in this chapter for the two institutions ancient civilizations serving and caring for orphans funds was the first in the city of Ramallah, a " Management Foundation and the development of the property of orphans, "where is this the only institution that sponsor and invest and develop the orphans themselves funds from being an official with a tightly controlled institution in the first section of this chapter, but in the second part, a charitable social institution has addressed namely" Islamic Charitable Society in Hebron "an association concerned with orphans through guarantees and with the donations collected and invest in order to be as well as orphans and caring for their own affairs. She concluded by mentioning Find Conclusion and some of the results and recommendations reached by.

الحمد لله رب العالمين، والصلاة والسلام على اشرف المرسلين، سيدنا محمد – صلى الله عليه وسلم – وبعد..... تناولت في هذه الدراسة موضوع " الضوابط الشرعية في إدارة وتنمية أموال الايتام دراسة تطبيقه رام الله والخليل نموذجا ". فألقيت الضوء على مدى اهتمام الفقه الإسلامي قديما وحديثا بالأيتام، من حيث رعايتهم، والأمر بالمحافظة على حقوقهم وخاصة المالية منها، وكيفية استثمار أموالهم وتنميتها ضمن الطرق والضوابط الشرعية ومن خلال كفالتهم، ورعايتهم، وتربيتهم، وتأديبهم، وتحريمَ الاعتداء على حقوقهم بأي شكل من الأشكال. فرعاية الأيتام في الإسلام مطلب شرعي، والقرآن الكريم حفل بذكر كثير من الأحكام والمواعظ التي تتعلق بشخص اليتيم. ولقد قسمت هذا البحث إلى مقدمة، و تمهيد، و أربعة فصول، و خاتمة، وقد بينت من خلال هذه الفصول الأربعة طرق العناية بمال اليتيم بعد ان عرفت اليتيم والولي للوصول الى افضل الطرق المشروعة لاستثمار مال اليتيم وتنميته. فتحدثت في الفصل الأول عن تعريف اليتيم لغة واصطلاحا، وعن أهمية الولاية على أموال اليتامى، وتطرقت في المبحث الثاني من هذا الفصل الى تعريف الولاية واقسامها ولمن تثبت له الولاية على مال اليتيم، اما في المبحث الثالث فتناولت شروط الولي على مال اليتيم، وسلطته في التصرف في ذلك المال حتى لا يكون من المعتدين على مال اليتيم وان لا يتصرف بماله الا بالتي هي احسن. اما الفصل الثاني فكان بعنوان مشروعية الاستثمار في أموال الايتام، وقد قسمت هذا الفصل الى مبحثين رئيسين، تحدثت في المبحث الأول عن مفهوم الاستثمار في لغة العرب واصطلاح العلماء الشرعيين والاقتصاديين، اما في المطلب الثاني تطرقت الى مشروعية الاستثمار من مصادر التشريع الأساسية معلقا عليها وشارحا، واختتمت هذا المبحث بذكر حكم الاستثمار في أموال الايتام بناء على ما أوردت من ادلة من القران الكريم والسنة الشريفة على مشروعيته. وفي المبحث الثاني بينت اهم المقاصد الشرعية في استثمار أموال اليتامى متطرقا للقواعد المقاصديه الضابطة للمعاملات المالية والمتعلقة بتشريع وتنظيم الأموال في المطلب الأول، اما في المطلب الثاني فناقشت اهم ضوابط الاستثمار المتعلقة بمال اليتيم سواء اكانت الشرعية ام الإدارية وحتى القانونية. اما الفصل الثالث فكان بعنوان طرق استثمار أموال اليتامى، وقد قسمت هذا الفصل الى مبحثين اساسين، بينت في المبحث الأول حكم اكل الولي من مال اليتيم وتصرفات الولي بمال اليتيم في عقود المعاوضات المالية مثل المضاربة والمساقاة والمزارعة وباقي الاحكام الفقهية المتعلقة ببيع الولي من مال اليتيم، وتناول المبحث الثاني طرق الاستثمار من خلال مؤسسة. اما الفصل الرابع والأخير فهو من اهم الفصول في بحثي هذا، اذ هو ثمرة وخلاصة بحثي حيث كان بعنوان دراسة ميدانية حول مؤسسة إدارة وتنمية امول الايتام في فلسطين، حيث بحثت في هذا الفصل عن مؤسستين عريقتين تخدم وترعى أموال الايتام، كانت الأولى في مدينة رام الله وهي "مؤسسة إدارة وتنمية أموال اليتامى " حيث تعد هذه المؤسسة الوحيدة التي ترعى وتستثمر وتنمي أموال اليتامى انفسهم من كونها مؤسسة رسمية ذات رقابة مشددة، في المبحث الأول من هذا الفصل، اما في المبحث الثاني فقد تناولت مؤسسة خيرية اجتماعية الا وهي " الجمعية الخيرية الإسلامية في مدينة الخليل " وهي جمعية تهتم باليتامى من خلال الكفالات وجمع التبرعات التي تجمعها، وتستثمر فيها حتى تكون الى جانب الايتام وترعى شؤونهم. وختمت البحث بذكر الخاتمة وبعض النتائج والتوصيات التي توصلت اليها.
الضوابط الشرعية في إدارة وتنمية صناديق أموال الأيتام في فلسطين "دراسة ميدانية الخليل ورام الله نموذجاً"